Crystallization Characteristics of B2O3 and TiO2-bearing Glassy Fluoride-Free Mold Fluxes - Wang, Zhen; Shu, Qifeng; Chou, Kuochih (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
To explore the effects of TiO2 and/or B2O3 on crystallization of the glassy fluoride-free slag film near the copper mould, the crystallization characteristics of glassy fluoride-free mold fluxes with fluoride being substituted by TiO2 and/or B2O3 were investigated using X- ray diffraction (XRD), scanning electron microscope (SEM) and differential thermal analysis (DTA) techniques. The glass forming ability index (Kgl) of the glassy fluoride-free mold fluxes was studied using Hruby’s method. The XRD and SEM analysis show that Ca2Al2SiO7, CaTiO3 and CaSiO3 are the dominant crystals of this fluoride-free mold fluxes system. With the content of TiO2 increasing from 0 to 7%, the crystallization of Ca2Al2SiO7 and CaSiO3 are inhibited and the formation of CaTiO3 is also weak, so crystallization tendency of the glassy fluoride-free mold fluxes weakens. But as TiO2 content reaches 10%, the crystallization tendency strengthens because of the strong crystallization of CaTiO3. An increase of B2O3 inhibits the crystallization of calcium silicate, so it weakens the crystallization tendency of the glassy fluoride-free mold fluxes. The crystallization processes of the studied fluoride-free mold fluxes correspond to the surface crystallization mechanism. This research provides important reference for further investigation on the heat transfer behavior of the TiO2 and B2O3-bearing slag between copper mould and slab to evaluate the feasibility of B2O3 and TiO2-bearing fluoride-free mold fluxes.